A Study of Traditional Mongol Law in Europe - Bayanbaatar, Batbayar; Enkhee, Tuulaikhuu (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
This brief study examines the historical evolution and codification of traditional Mongol laws and their role in shaping governance from antiquity to the early 20th century. The paper is organized into three parts: an overview of key Mongolian legal sources – including the Great Yasa, Yuan legal codes, and various edicts – an analysis of European contributions that systematized Mongol legal traditions through pioneering Russian and German scholarship, and a discussion of future directions in Mongol legal research. Emphasizing interdisciplinary methodologies and the translation of historical texts, this work aims to enhance global accessibility to Mongolia’s legal heritage and stimulate further comparative legal studies.